From Awareness to Action: Decoding the Green Gap in Sustainable Fashion Consumption Using the Information-Motivation-Behavioral Skills - Tiara Nur Anisah; Eri Haryanto; Andika; Pooja Nanda; Daniel Wandika (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2026)
Objective: This study aims to decipher the "attitude-behavior gap" in the sustainable fashion market by adapting the Information-Motivation-Behavioral Skills (IMB) model. It investigates how Sustainable Awareness (Information) and Intrinsic Motivation influence Sustainable Consumption Behavior Intention, with a specific focus on Green Self-Efficacy as the central mediating mechanism. Design/Methods/Approach: A quantitative research design was employed, utilizing primary data collected from 235 consumers via an online survey. The hypothesized relationships within the IMB framework were tested using Partial Least Squares Structural Equation Modeling to ensure robust predictive validity. Findings: The empirical analysis reveals a significant anomaly: Sustainable Awareness does not directly influence purchase intention, confirming that environmental knowledge alone is insufficient to drive action. Conversely, Intrinsic Motivation emerges as a strong direct predictor. Crucially, Green Self-Efficacy functions as a pivotal bridge; it fully mediates the relationship between awareness and intention, and acts as a partial mediator for intrinsic motivation. Originality/Value: This study contributes to the existing literature on sustainable consumer behavior by adapting the IMB model, typically restricted to health psychology, to the context of fashion marketing in an emerging economy. Unlike previous research that relies heavily on the Theory of Planned Behavior, this study demonstrates that bridging the "green gap" requires a capability-based approach, validating that Green Self-Efficacy is the critical mechanism required to translate passive awareness into active purchasing intentions. Practical/Policy implication: Given the results, managers should shift their strategies from simple environmental education to consumer empowerment. Managers are advised to enhance green self-efficacy through transparent labeling and "lifestyle" narratives that simplify decision-making, thereby helping consumers feel competent to translate their intrinsic motivation into actual purchasing behavior. Additionally, policy initiatives should focus on removing pragmatic barriers to support this transition.